Rosyid Ridho OPTIMALISASI KETERAMPILAN BERBICARA MELALUI METODE MUHA - Rosyid Ridho (Institut Agama Islam Darusssalam Blokagung, 2023)
The Arabic language takhassus hostel at the Darussalam Blokagung Islamic Boarding School is one of the focus areas for studying Arabic. In practice learning Arabic is greatly assisted by the muhawarah method, which is one of the many methods used to support the realization of the results of learning Arabic especially in the category of Arabic speaking proficiency. In addition to the need for the habit of speaking in Arabic, vocabulary is very important in speaking skills. The muha>warah method is said to be more optimal in improving speaking skills. This method aims to improve students' ability to use the vocabulary they already have and to train students' courage in expressing their opinions. The method used by the researchers in this study was a descriptive qualitative method, the source of which was obtained from observations during the learning process of speaking skills using the muha>warah method and also the results of interviews with supporting teachers and Arabic language takhassus dormitory students. Data analysis is applied using triangulation analysis of data sources that seek the validity of certain information by using various data sources including documents, archives, interview results, observation results or by interviewing more than one subject who is assumed to have different perspectives